Halitosis and Quality of Life in Young Orthodontic Patients: A Cross-Sectional Assessment of Mouthwash Use and Traditional, Rotative, and Sonic Toothbrushes - Hamsah Musa; Ioana Georgiana Pașca; Malina Popa; Octavia Bălean; Ramona Dumitrescu; Ruxadra Sava Roșianu; Atena Gălușcan; Roxana Oancea (Medicina)
Background and Objectives: Halitosis is common among orthodontic patients, potentially exacerbated by plaque retention around brackets. It was hypothesized that patients using sonic toothbrushes would report lower halitosis impact scores compared to those using traditional or rotative toothbrushes. This study aimed to compare the Halitosis-Associated Life Quality Test (HALT) and Short Form (SF-36) domains among different toothbrush users and to evaluate mouthwash subgroups and “during” vs. “after” appliance removal. Methods: Based on a power calculation (effect size f = 0.30, α = 0.05, 1 − β = 0.80), 174 patients were required. A total of 174 orthodontic patients (57 traditional, 64 rotative, and 53 sonic; mean age 18.0 ± 1.5 years) completed the Halitosis-Associated Life Quality Test (HALT), SF-36, and organoleptic assessments. Results: Sonic toothbrush users reported significantly lower HALT scores (34.8 ± 5.8) vs. rotative (38.1 ± 6.0) and traditional (42.7 ± 6.2) toothbrush users. Spearman’s correlation (r = −0.49 to +0.54) demonstrated that sonic brushing had a moderate negative relationship with halitosis scores, indicating lower malodor for this technique. Patients using chlorhexidine-based mouthwash had the most favorable HALT (34.3 ± 5.7) and organoleptic (1.5 ± 0.4) scores. Those who completed orthodontic treatment showed better outcomes than active treatment patients. Conclusions: Optimized plaque control with sonic brushing and chlorhexidine-based mouthwash correlates with reduced halitosis and improved quality of life during orthodontic treatment.